Microbial ecology of sulfur cycling near the sulfate–methane transition of deep‐sea cold seep sediments - Li, Wen‐Li; Dong, Xiyang; Lu, Rui; Zhou, Ying‐Li; Zheng, Peng‐Fei; Feng, Dong; Wang, Yong (Environmental microbiology, 2021)
Summary Microbial sulfate reduction is largely associated with anaerobic methane oxidation and alkane degradation in sulfate–methane transition zone (SMTZ) of deep‐sea cold seeps. How the sulfur cycling is mediated by microbes near SMTZ has not been fully understood. In this study, we detected a shallow SMTZ in three of eight sediment cores sampled from two cold seep areas in the South China Sea. One hundred ten genomes representing sulfur‐oxidizing bacteria (SOB) and sulfur‐reducing bacteria (SRB) strains were identified from three SMTZ‐bearing cores. In the layers above SMTZ, SOB were mostly constituted by Campylobacterota, Gammaproteobacteria and Alphaproteobacteria that probably depended on nitrogen oxides and/or oxygen for oxidation of sulfide and thiosulfate in near‐surface sediment layers. In the layers below the SMTZ, the deltaproteobacterial SRB genomes and metatranscriptomes revealed CO2 fixation by Wood–Ljungdahl pathway, sulfate reduction and nitrogen fixation for syntrophic or fermentative lifestyle. A total of 68% of the metagenome assembled genomes were not adjacent to known species in a phylogenomic tree, indicating a high diversity of bacteria involved in sulfur cycling. With the large number of genomes for SOB and SRB, our study uncovers the microbial populations that potentially mediate sulfur metabolism and associated carbon and nitrogen cycles, which sheds light on complex biogeochemical processes in deep‐sea environments.